Diversity of Narrative Functionality in Short Fiction Films - Jamal Al-Deen Jamal Lutfi; Dr. Barrak A. Ahmad Zaki (Zien Journals, 2022)
Finding a balance between using and employing complex narrative techniques and clearly conveying the idea to the recipient in short fiction films. 2- Finding solutions to the problems of time gaps in the narrative building of a short film. 3- Revealing the various narrative functions within the structure of the short film. The research relied on a (case study) represented in a film sample according to a descriptive analysis because it fits the nature of the research depending on a clear and specific tool, and the research community is short fiction films, and the research results are: - Control of time and intensification is the biggest challenge that the short film maker is faced with in order to make a coherent narrative building according to a balanced plot that is not naive nor complex.
Keywords: Diversity of narrative functionality; short fiction film